Reaksi Pasar Terhadap Kenaikan Harga Bahan Bakar Minyak (BBM) Tanggal 24 Februari 2018 ( Studi Kasus Perusahaan Indeks LQ45) - Lisa, Hilaria Lisa B1021131082 (Jurnal Manajemen Update, 2018)
ABSTRACTThis research aims at analyzing market reaction to the fuel price hike (BBM) dated February 24th 2018 on LQ45 index company which is listed in Indonesia stock exchange (BEI). This reseach use secondary data for the data collection. The method of sampling uses sampling saturation. The company us as sample object ws company listed on the LQ45 in Stock Exchange Indonesia (BEI) for the period of February to July 2018. The selection fm the sample of companies was based on the companies included in LQ45 index that already fulfilled criteria in this case there are 45companies that become the sample of this study. The research method use is the method Event Study, with 100 days estimation period and 11 days windows period. The test was using the data normality test tool Kolmogorov Smirnov and the deffernt test equipment Paired sample-test.Based on data analysis the fuel price hike (BBM) dated February 24th 2018 did not cause any significant abnormal return at the time of event as well as on research defference of mean of abnormal return and trading volume activity on the day before and after the result that there is no significant market reaction. This mean the fuel hike price hike (BBM) dated February 24th, 2018 is something that does not have too much positive influence on the Indonesian stock market.Keyword: Stock Market, Event Study,Abnormal Return, Trading Volume ActivityDAFTAR PUSTAKAFama, eugene f. 1991. Efficient Capital Market II. Journal of Finance. Desember. 66(5), pp:1-21Hamdani, P. B. (2015). Statistika Deskriptif dalam Bidang Ekonomi dan NiagaHartono, Jogiyanto. 2012. Teori Portofolio dan Analisis Investasi Edisi ke 2. BPFE.YogyakartaHusnan, Suad, (1998), Dasar-dasar Teori Portofolio dan Analisis Sekuritas, edisi dua, Yogyakarta, AMP YKPNIrham,Fahmi dan Hadi,Yovi L 2011. Teori Portofolio dan Analisis Investasi. Alfabeta, Bandung.Markowitz, H. M. 1952, Portfolio Selection, Journal of Finance,pp: 77-91. Marwata, 2000, Kinerja Keuangan, Harga Saham Dan Pemecahan Saham, Seminar Nasional Akuntansi (3):h:751-769.Rusdin, 2018. Pasar Modal : Teori, masalah dan kebijakan dalam praktik. Alfabeta Bandung. Samsul, Mohamad. 2006. Pasar Modal & Manajemen Portofolio. Jakarta: Erlangga. Sari, Puspita. 2013. Tempo. Berita dipublikasikan. Diakses tanggal 12 Juni 2018. Tandelilin, Eduardus. 2007. Analisis Investasi dan Manajemen Portofolio Edisi Pertama. Yogyakarta: BPFE-Yogyakarta.Tandelilin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi, Edisi Pertama. YogyakartaTjipto,Darmadji dan Fakhuruddin,M Hendry, 2001. Pasar Modal di Indonesia.Salemba Empat, Jakarta.www.idx.co.id diakses Februari 2018www.ksei.com diakses Maret 2018www.sahamok.com diakses Februari 2018www.yahoofinance.com diakses Maret 2018